Use of carbon meshes containing carbon nanofibers

By a carbon mesh that is mixed with porous crystal nano -carbon fiber that is mixed with porous in plastic materials, the problem of static electricity accumulation is solved, and the accurate control of the conductivity and the reduction of static electricity risks.

CN112424272BActive Publication Date: 2025-01-28CAPONCOS IP5 PTY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201980043883.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-05-25
Filing Date
2019-05-27
Publication Date
2025-01-28
Estimated Expiration
2039-05-27

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the accumulation of static electricity in plastic materials, resulting in uncontrolled release of static charges, which may cause product failure, fire or explosion.

Method used

Carbon mesh containing a chemical -interacting crystalline nano -carbon fiber is used to accurately control the volume resistivity by increasing the conductivity by mixing the material in the layer to improve the conductivity and the adjustment level of the carbon mesh.

Benefits of technology

The precise control of the conductivity of the electrostatic layer, electrostatic dispersing layer or conductive layer is realized, reducing the accumulation and release risk of static charge, and at the same time improve the processing of materials, allowing a thinner film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002865232060000201
    Figure BDA0002865232060000201
  • Figure BDA0002865232060000211
    Figure BDA0002865232060000211
  • Figure BDA0002865232060000212
    Figure BDA0002865232060000212
Patent Text Reader

Abstract

The present invention relates to the use of a porous carbon network containing chemically interconnected isotropic nanocarbon fibers in an antistatic layer, static dissipative layer or conductive layer having a thickness of less than 1000 μm. It has been found that the carbon network containing nanocarbon fibers can be beneficially used in antistatic layers or static dissipative layers where the surface or volume resistivity needs to be carefully controlled. It has also been found that the viscosity of the composite is weakly responsive to the carbon network, which allows the drawing of high quality layers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of antistatic materials, static dissipative materials or (semi)conductive materials, in particular to the field of preparing sheets or films. Technical Background

[0002] Control of static electricity accumulation is considered important in many technical fields, especially in the field of electronic devices. Plastic materials seem to be ubiquitous and are particularly prone to becoming statically charged. Typically, plastics have high electrical resistance and allow little, if any, charge to move on their surface or in their body. Plastics are therefore considered insulating materials. When two insulators in close range move relative to each other, charge can accumulate. The two insulators will become positively or negatively charged. This accumulation of charge is called static electricity and is often unwanted. Not only can it cause plastic films and / or sheets to stick to each other, which can be problematic from a factory production perspective and can lead to an unsatisfactory consumer experience. And it can also lead to product failure, especially in the case of electronic products where low voltage discharges can cause serious damage to sensitive products. And, perhaps the most obvious adverse effect is that the discharge of static charge can lead to hazards such as fire or explosion.

[0003] The accumulation of static charge can be prevented by using a film of conductive material that is properly grounded. Alternatively, antistatic or static dissipative materials can be used. These are materials that have a lower conductivity than conductors but higher than insulators. Or, in other words, a higher resistivity than conductors but lower than insulators. The increase in resistivity prevents the uncontrolled release of energy that can occur when using fully conductive materials.

[0004] It is known that the accumulation of static charge on plastics during factory handling or use can be prevented by using electrostatic dissipative (ESD) materials. If beneficial, the article can be made entirely of ESD materials such as ESD packaging or ESD films. However, the article can also be coated with an ESD film or layer so that suitable electrostatic protection is achieved. The conventional technique for increasing the conductivity of an insulator and thus preparing an ESD material is to incorporate an antistatic agent or a conductive agent. A typical example of such an agent is carbon black. For example, in WO2014 / 108876, it is described how carbon black and non-conductive polymers can be used to prepare thermoplastic ESD composites.

[0005] In general, the challenge with carbon fillers is to precisely control the desired resistivity value based on the steep permeation curves associated with these materials. Carbon fillers are known to have properties whereby small changes in dosage (which can be as little as 1 wt%) can result in drastic changes in conductive properties (from completely insulating to completely conductive, or vice versa). This in turn can result in unwanted and uncontrolled release of energy in articles containing materials with such carbon fillers due to static charge accumulation.

[0006] It is therefore desirable to expand the permeation slope, which will mean an increased dosage tolerance or an expanded dosage window. This in turn can allow better control of the resistivity value and in particular adjustment of the conductivity. However, currently known antistatic or conductive agents are often difficult to handle. This includes problems related to the dispersion method and the changes in the material properties caused by the antistatic or conductive agent. For example, it is known that carbon black increases the viscosity of the material to which it is added. Therefore, an ESD composite material comprising an insulating material and carbon black will have a much higher viscosity than an insulating material without carbon black. This increase in viscosity is undesirable from a production perspective and leads to various production problems. An example of such a problem is poor dispersion due to increased viscosity, which in turn can lead to subsequent negative consequences, such as brittle materials. For the preparation of layers or films, it is necessary to have a fairly low viscosity. If the melt used to prepare the layer has an excessively high viscosity, it is simply impossible to achieve a sufficiently low thickness. Therefore, current technology is limited with respect to the preparation of ESD layers.

[0007] There is therefore a need to solve the problem of obtaining an antistatic layer, a static dissipative layer or a conductive layer having a sufficiently low thickness and the desired ESD properties. Summary of the invention

[0008] The inventors have found that the newly developed grade of carbon mesh containing nanocarbon fibers can be beneficially used in layers (i.e., films or sheets) with a thickness of less than 1000 μm. The carbon mesh containing nanocarbon fibers is a porous carbon mesh containing chemically interconnected nanocarbon fibers, which can be incorporated into the layer using conventional preparation techniques. The carbon mesh containing nanocarbon fibers is particularly useful for increasing the conductivity of the layer. The addition level of the carbon mesh can be selected as needed, but should generally be greater than 10% by weight of the layer. Reference Examples.

[0009] The porous carbon network containing chemically interconnected crystalline nanocarbon fibers advantageously allows precise control of the resistivity of the layer in which the carbon network is embedded. In other words, upon increasing the level of incorporation of the carbon network, the volume resistivity decreases only gradually. A typical graph of the level of incorporation of the carbon network versus the volume resistivity would show high volume resistivity at low incorporation levels (e.g., 10 12 Ω.cm), at a certain addition level (e.g., about 15 wt%), the volume resistivity will begin to slowly decrease until it reaches a lower volume resistivity (e.g., 10 wt%) at a higher addition level (e.g., about 30 wt%). 2Ω.cm). Therefore, the dosing window (dosing window) (sometimes also expressed as (dosing) tolerance in the art) of the controllable volume resistivity is about 15 wt%. This high dosage window of at least 6 wt%, more preferably at least 12 wt%, even more preferably at least 14 wt% and most preferably at least 16 wt% is very beneficial for the preparation of antistatic layers, static dissipative layers or conductive layers. This behavior is in sharp contrast to the behavior of carbon black, carbon nanotubes, graphite, etc., which suddenly change from insulation to conductivity in a dosage window of about 1 wt%. In such a small window, there is no opportunity to accurately adjust the volume resistivity of the layer. On the other hand, due to the large dosage tolerance, the porous carbon mesh containing chemically interconnected crystalline nano-carbon fibers allows the volume resistivity of the layer to be carefully adjusted, for example, to within the antistatic range (within 10 8 Ω.cm and 10 10 Ω.cm) or in the static dissipative range (between 10 4 Ω.cm and 10 8 Ω.cm).

[0010] The manufacturing shows advantages in terms of melt flow index (MFI) and melt strength. MFI is a measure of the flow resistance of a polymer, and melt strength is defined as the maximum tension that can be applied to a melt without breaking. Both are important parameters for preparing films, and favorable MFI and melt strength make it possible to prepare homogeneous films, while materials such as carbon black fail. MFI is defined as the mass of a polymer that flows through a capillary of a hole or tool with a specific thickness and weight at a specific pressure and temperature. High viscosity therefore corresponds to low MFI, and vice versa. Porous carbon meshes containing chemically interconnected crystalline nano-carbon fibers show beneficial behavior in terms of viscosity and melt flow index (MFI) of compounds in which they are present. For example, when polypropylene copolymer (PPC) is loaded with 20% by weight carbon mesh or Vulcan XC72 (a carbon black grade often used to improve the conductivity of a material), it has been found that the MFI of the PPC using the carbon mesh is three times higher than the MFI of the PPC using Vulcan XC72. Thus, at those addition levels associated with the conductive layer, composites using carbon networks have lower viscosities than composites using carbon black, making the formation of films or sheets from composites having carbon networks relatively easy to handle and allowing thin films to be prepared in a more reliable manner.

[0011] It will therefore be appreciated that porous carbon meshes containing chemically interconnected crystalline nanocarbon fibers are particularly suitable for use in conductive layers, sheets and (thin) films. This allows for careful control of the conductive properties and adjustment of the volume resistivity. In addition, because the viscosity of the composite mixture will be relatively low, it allows for the preparation of thinner films compared to current prior art.

[0012] The layer may be an antistatic layer, a static dissipative layer or a conductive layer. The volume resistivity may thus be less than 10 10 Ω.cm. In some applications, it is desirable to adjust the volume resistivity to 10 4 with 10 10 In other embodiments, it is desirable to obtain a range of <10 4 In the art, layers comprising conductive carbon are sometimes also referred to as semiconductive to indicate that they actually conduct electricity, but have not yet reached the conductivity of metals. The same term also applies to these layers of the present invention.

[0013] The network may comprise crystalline nanocarbon fibers, which may have an average length of about 30 to 10,000 nm. The porous network may be considered a macromolecule and may therefore be described as an intraparticle porous network.

[0014] The layers comprising the carbon mesh of the present invention can be made of a variety of materials, but are typically polymer layers. These layers comprising the carbon mesh of the present invention can be suitable for use in many technical fields, including packaging materials, electrodes, batteries, water purification, microelectronic devices, microchip and wafer production, electromagnetic shielding, and thin film solar cells as well as coatings and even deposited inks.

[0015] The invention also encompasses the use of a porous carbon network comprising chemically interconnected carbon nanofibers for reducing the thickness of a layer comprising carbon nanofibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1A Schematic diagram of the continuous furnace carbon black preparation method according to the present invention, which contains a combustion zone 3a, a reaction zone 3b and a termination zone 3c along the axis of the reactor 3, and the crystalline carbon network of the present invention is obtained by the following operations: preparing hot exhaust gas a1 by burning fuel a in an oxygen-containing gas b in the combustion zone and transferring the exhaust gas a1 from the combustion zone 3a to the reaction zone 3b; spraying (atomizing) a single-phase emulsion c in the reaction zone 3b containing the hot exhaust gas; carbonizing the emulsion at an elevated temperature; and stopping or quenching the reaction in the termination zone 3c by spraying water d;

[0017] Figure 1B Schematic diagram of a semi-batch carbon black preparation process, wherein a single-phase emulsion c is atomized into a reaction zone 3b at an elevated temperature via a nozzle 4 at the top of a reactor 3; the emulsion is carbonized at an elevated temperature in the reaction zone 3b; and a crystalline carbon network e is collected at the bottom of the reactor. In addition, there are two gas inlets entering the reactor from the top, which are used to add an inert gas f, preferably nitrogen, for controlling and / or consuming oxygen levels, and for introducing a carbon-containing gas g, preferably acetylene or ethylene, into the reactor.

[0018] Embodiments of the present invention

[0019] 1. Use of a porous carbon network comprising chemically interconnected nanocarbon fibers in an antistatic layer, static dissipative layer or conductive layer, the layer having a thickness of less than 1000 μm;

[0020] 2. The use according to embodiment 1, wherein the use is for increasing the conductivity of an antistatic layer, a static dissipative layer, a semiconductive layer or a conductive layer;

[0021] 3. The use according to any of the preceding embodiments, wherein the carbon network is incorporated at a level greater than 10% by weight of the layer;

[0022] 4. an antistatic layer, static dissipative layer, semiconductive layer or conductive layer having a thickness of less than 1000 μm, preferably less than 250 μm, comprising at least 10% by weight of a porous carbon network comprising chemically interconnected nanocarbon fibers;

[0023] 5. The use according to any one of embodiments 1 to 3 or the layer according to embodiment 4, wherein the carbon network comprises crystalline nanocarbon fibers;

[0024] 6. The use according to any one of embodiments 1 to 3 or 5 or the layer according to embodiment 4 or 5, wherein the carbon network is an intragranular porous network;

[0025] 7. The use according to any one of embodiments 1 to 3 or 5 to 6 or the layer according to any one of embodiments 4 to 6, wherein the average fiber length of the nanocarbon fibers is 30 to 10,000 nm;

[0026] 8. The use according to any one of embodiments 1 to 3 or 5 to 7 or the layer according to any one of embodiments 4 to 7, wherein the layer is a polymer layer;

[0027] 9. The use according to any one of embodiments 1 to 3 or 5 to 8 or the layer according to any one of embodiments 4 to 8, wherein the volume resistivity is 10 0 -10 10 Ω.cm;

[0028] 10. The use according to any one of embodiments 1 to 3 or 5 to 9 or the layer according to any one of embodiments 4 to 9, wherein the carbon network can be obtained by a method for preparing a crystalline carbon network in a reactor 3 containing a reaction zone 3b and a termination zone 3c by the following operations: injecting a water-in-oil or bicontinuous microemulsion c containing metal catalyst nanoparticles into a reaction zone 3b at a temperature above 600°C, preferably above 700°C, more preferably above 900°C, even more preferably above 1000°C, more preferably above 1100°C, preferably at most 3000°C, more preferably at most 2500°C, most preferably at most 2000°C, to prepare a crystalline carbon network e; transferring these networks e to the termination zone 3c; and quenching or stopping the formation of the crystalline carbon network in the termination zone by spraying water d;

[0029] 11. An article comprising a layer according to any one of embodiments 4 to 10;

[0030] 12. The article according to embodiment 11, wherein the layer is a deposited ink, an applied coating, or a packaging material; and

[0031] 13. Use of a porous carbon network comprising chemically interconnected nanocarbon fibers for reducing the thickness of a layer comprising nanocarbon fibers, preferably to a thickness of less than 1000 μm, preferably less than 250 μm. DETAILED DESCRIPTION

[0032] The present invention can be described as the use of a porous carbon mesh containing chemically interconnected nano-carbon fibers in a conductive layer having a thickness of less than 1000 μm. Conveniently, a layer of 250-1000 μm is represented as a sheet, and a thinner layer, i.e. a layer of less than 250 μm, is represented as a membrane or film. In this article, we will abide by these definitions of "sheet" and "film". Preferably, the sheet according to the present invention is thinner than 750 μm, more preferably thinner than 500 μm and most preferably thinner than 350 μm. The film according to the present invention is preferably thinner than 200 μm, even more preferably thinner than 150 μm, still more preferably thinner than 100 μm, still more preferably thinner than 75 μm, still even more preferably thinner than 50 μm and most preferably thinner than 25 μm. The use of a carbon mesh in a membrane can appropriately increase the conductivity of the membrane and / or reduce the resistivity of the membrane. The resistivity can be surface and / or volume resistivity. The resistivity or conductivity can be measured with the aid of a Keithley picoammeter.

[0033] It will be understood by those skilled in the art that a porous network refers to a 3-dimensional structure that allows fluid or gas to pass through. A porous network may also be represented as a porous medium or porous material. As measured using the Brunauer, Emmett and Teller (BET) method (ASTM D6556-09), the pore volume of the porous carbon network according to the present invention is 0.1 to 1.5 cm 3 / g, preferably 0.2 to 1.5 cm 3 / g, more preferably 0.3 to 1.3 cm 3 / g and most preferably 0.4 to 1.3 cm 3 / g.

[0034] The carbon network containing nanofibers may have an intraparticle pore diameter of 5 to 150 nm, preferably 10 to 120 nm, and most preferably 10 to 100 nm, as measured using mercury intrusion porosimetry (ASTM D4404-10).

[0035] The carbon mesh comprising nanofibers may have a porosity of 0.10 to 1.1 cm as measured using mercury intrusion porosimetry (ASTM D4404-10). 3 / g, preferably 0.51 to 1.0 cm 3 / g, and most preferably 0.59 to 0.91 cm 3 / g of intragranular volume.

[0036] The porous carbon mesh according to the present invention (or the porous carbon mesh particles of the present invention) can be regarded as macromolecules, in which carbon atoms are inherently interconnected in a covalent manner. It will be understood that the porous carbon mesh particles are particles of chemically interconnected (i.e., covalently bonded) fibers with intragranular porosity, which is opposite to the interparticle porosity of a porous mesh established by multiple molecules or particles and in which the pores are formed by the spaces between physically aggregated particles or molecules. In the context of the present invention, the intragranular porosity can also be expressed as intramolecular porosity, because the carbon mesh particles according to the present invention can be regarded as macromolecules, in which the pores are embedded. Therefore, intragranular porosity and intramolecular porosity have the same meaning and can be used interchangeably to describe the porous mesh of the present invention in this article. Compared with traditional carbon black that does not have an intragranular pore structure in the carbon black particles, the aggregates of carbon black particles can also have interparticle porous properties. Although the interparticle / intramolecular is the space between physically aggregated particles (mesh), the intraparticle / intramolecular is the space within the mesh itself.

[0037] Without being limited by theory, it is believed that the benefit of a mesh with intra-particle porosity over a mesh with inter-particle porosity is that the former is stronger and more resilient in resisting crushing and breaking when force is applied. Intra-particle porosity refers to the pores present within the (nano)particles. Inter-particle porosity refers to the pores present as a result of stacking the particles. Inter-particle pores are weak and tend to collapse due to the particle-particle interface. Intra-particle pores are strong and can withstand large forces and pressures without collapse due to the covalently bonded structure surrounding these pores.

[0038] As described above, it is known that reinforcing agents such as carbon black are composed of aggregates or agglomerates of spherical particles that can form a 3-dimensional structure but do not have any covalent bonds (non-"chemical interconnections") between the particles, and therefore have inter-particle porosity. In general, intra-particle porosity refers to the situation where the carbon atoms surrounding the pores are covalently bonded, where as inter-particle porosity refers to the pores existing between particles that are physically aggregated, agglomerated, or the like.

[0039] Since the mesh of the present invention can be regarded as a macromolecule, it is not necessary to fuse the particles or parts of the mesh together. Therefore, preferably, the porous network of chemically interconnected nanocarbon fibers is a non-fused intragranular porous carbon mesh containing chemically interconnected nanocarbon fibers with intragranular porosity. In a preferred embodiment, the intragranular pore volume can be characterized in the following aspects as further described below: for example, mercury intrusion porosimetry (Mercury Intrusion Porosimetry) (ASTM D4404-10) or Bruno, Emmett and Teller (BET) method (ISO9277; 10).

[0040] The technician will readily understand that the term chemical interconnection in the porous carbon mesh containing chemically interconnected nano-carbon fibers implies that the nano-carbon fibers are interconnected to other nano-carbon fibers by chemical bonds. It should also be understood that chemical bonds are synonyms for molecules or covalent bonds. Typically, those places where nano-carbon fibers are connected are expressed as junctions or fiber junctions, which can therefore be conveniently referred to as "covalent junctions". These terms are used interchangeably in this article. In the carbon mesh according to the present invention, the junctions are formed by covalently connected carbon atoms. And therefore, the length of the fiber is defined as the distance between the junctions connected by the fiber carbon material.

[0041] At least a portion of the fibers in the mesh of the nanofibers of the present invention are crystalline nanofibers. Preferably at least 20% by weight, more preferably at least 40% by weight, even more preferably at least 60% by weight, even more preferably at least 80% by weight and most preferably at least 90% by weight of the carbon in the carbon mesh of the present invention is crystalline. Alternatively, the amount of crystalline carbon is 20 to 90% by weight, more preferably 30 to 70% by weight and more preferably 40 to 50% by weight compared to all the carbon in the carbon mesh of the present invention. Herein, crystallization has its usual meaning and refers to the degree of structural order in the material. In other words, the carbon atoms in the nanofibers are arranged in a regular periodic manner to some extent. The crystallized area or volume can be expressed as a crystallite. Therefore, a carbon crystallite is a single carbon crystal. The measure of the size of a carbon crystallite is the stacking height of graphite layers. The standard ASTM grade of carbon black has a stacking height of graphite layers within these crystallites of 11 to 150%. The carbon mesh containing nano-carbon fibers of the present invention has at least (Angstroms), preferably at least More preferably at least Even more preferably at least Even more preferably at least and still more preferably at least If desired, stack heights of up to Therefore, the carbon network of the present invention has a maximum (angstroms), more preferably at most Even more preferably at most Even more preferably at most Still more preferably at most Therefore, it should be understood that the stacking height of the graphite layers in the microcrystals in the carbon network of the present invention is 15 to (Angstroms), more preferably 16 to Even more preferably, 17 to Still more preferably 18 to And most preferably 19 to

[0042] The porous carbon mesh containing chemically interconnected nanocarbon fibers can be defined as having chemically interconnected nanocarbon fibers, wherein the nanocarbon fibers are interconnected via a junction, wherein several (usually 3 or more, preferably at least 10 or more) nanofibers are covalently linked. The nanocarbon fibers are those parts between the junctions in the mesh. The fiber is typically a solid (i.e. non-hollow) elongated body, preferably having an average diameter or thickness of 1 to 500nm, preferably 5 to 350nm, more preferably up to 100nm, and 50 to 100nm in one embodiment, compared to the average particle size of 10nm to 400nm of carbon black particles. In one embodiment, as can be determined, for example, using SEM, the average fiber length (i.e., the average distance between two junctions) is preferably in the range of 30 to 10,000nm, more preferably 50 to 5,000nm, more preferably 100 to 5,000nm, more preferably at least 200 to 5,000nm.

[0043] Nanofibers or structures may preferably be described as having an average aspect ratio of fiber length to thickness of at least 2, preferably at least 3, more preferably at least 4 and most preferably at least 5, preferably at most less than 50; in sharp contrast to the amorphous (physically united) aggregates formed by spherical particles obtained by conventional carbon black manufacturing.

[0044] Nano carbon fiber structure can be defined as a carbon mesh formed by chemically interconnected nano carbon fibers. These carbon meshes have a 3-dimensional configuration, wherein there is an opening for continuous phase to enter between nano carbon fibers, and the continuous phase can be a liquid, such as a solvent or an aqueous phase, a gas or any other phase. The carbon mesh has a diameter of at least 0.5 μm, preferably a diameter of at least 1 μm, preferably a diameter of at least 5 μm, more preferably a diameter of at least 10 μm, even more preferably a diameter of at least 20 μm, and most preferably 25 μm in all dimensions. Alternatively, the carbon mesh has a diameter of at least 1 μm in 2 dimensions, and has a diameter of at least 5 μm, preferably a diameter of at least 10 μm, more preferably a diameter of at least 20 μm and most preferably a diameter of at least 25 μm in another dimension. Here, and also throughout the entire text, the term dimension is used in a normal manner and refers to a spatial dimension. There are 3 spatial dimensions, which are orthogonal to each other and define space with its usual physical meaning. Furthermore, it is possible that the carbon network has a diameter of at least 10 μm in 2 dimensions and a diameter of at least 15 μm, preferably a diameter of at least 20 μm, more preferably a diameter of at least 25 μm, more preferably a diameter of at least 30 μm and most preferably a diameter of at least 50 μm in another dimension.

[0045] The carbon network comprising carbon nanofibers may have a volume-based aggregate size of 0.1 to 100 μm, preferably 1 to 50 μm, more preferably 4 to 40 μm, more preferably 5 to 35 μm, more preferably 6 to 30 μm, more preferably 7 to 25 μm, and most preferably 8 to 20 μm, as measured using laser diffraction (ISO 13320) or dynamic light scattering analysis.

[0046] The surface area of ​​the carbon network comprising nanofibers is preferably in the range of 40 to 120 m2 as measured according to the Brunauer, Emmett and Teller (BET) method (ISO 9277:10). 2 / g, more preferably 45 to 110 m 2 / g, even more preferably 50 to 100 m 2 / g and most preferably 50 to 90 m 2 / g range.

[0047] The porous carbon mesh of the nano-carbon fiber containing chemical interconnection can also include the carbon black particles built into the part of the mesh. These particles are found in large quantities at the junction between the nano-carbon fibers, but carbon black particles can also be present at other parts of the mesh. The diameter of the carbon black particles is preferably at least 0.5 times of the diameter of the nano-carbon fiber, more preferably at least the same as the diameter of the nano-carbon fiber, even more preferably at least 2 times of the diameter of the nano-carbon fiber, even more preferably at least 3 times of the diameter of the nano-carbon fiber, still more preferably at least 4 times of the diameter of the nano-carbon fiber and most preferably at least 5 times of the diameter of the nano-carbon fiber. Preferably, the diameter of the carbon black particles is at most 10 times of the diameter of these nano-carbon fibers. Such a mixed mesh is called a hybrid network.

[0048] The porous carbon mesh containing chemically interconnected nano carbon fibers has a functionalized surface. In other words, the surface contains groups that change the hydrophobic properties of the surface (which is typical for carbon) into more hydrophilic properties. The surface of the carbon mesh contains carboxyl groups, hydroxyl groups and phenolic compounds. These groups increase polarity for the surface and can change the properties of the compound material embedded with the functionalized carbon mesh. Without wishing to be limited by theory, it is now believed that the functionalized groups are combined with elastomers, for example, by forming H bonds, and thus increase the elasticity of the material. Therefore, at least the stiffness and durability of the material are changed, which can cause the rolling resistance of the tire or conveyor belt containing the reinforced elastomer to be reduced and the service life limit to increase.

[0049] The porous carbon mesh containing chemically interconnected nano-carbon fibers may contain metal catalyst nanoparticles. They are the fingerprint of the preparation method. These particles may have an average particle size of 1 nm to 100 nm. Preferably, the particles are monodisperse particles with a deviation of less than 10%, more preferably less than 5% from their average particle size. Non-limiting examples of nanoparticles included in these carbon mesh containing nano-carbon fibers are noble metals (Pt, Pd, Au, Ag), iron group elements (Fe, Co and Ni), Ru and Cu. Suitable metal complexes may be: (i) platinum precursors, such as H 2 PtCl 6 ;H 2 PtCl 6 .xH 2 O;K 2 PtCl 4 ; K 2 PtCl 4 .xH 2 O;Pt(NH 3 ) 4 (NO 3 ) 2 ; Pt(C 5 H 7 O 2 ) 2 , (ii) a ruthenium precursor, such as Ru(NO)(NO 3 ) 3 ;Ru(dip) 3 Cl 2 [dip=4,7-diphenyl-1,10-phenanthroline]; RuCl 3 , or (iii) a palladium precursor, such as Pd(NO 3 ) 2 , or (iv) a nickel precursor such as NiCl 2 or NiCl 2 .xH 2 O;Ni(NO 3 ) 2 ;Ni(NO 3 ) 2 .xH 2 O;Ni(CH 3 COO 2 ; Ni(CH 3 COO 2 .xH 2 O;Ni(AOT) 2 [AOT=bis(2-ethylhexyl)sulfosuccinate], where x can be any integer selected from 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 and typically can be 6, 7 or 8.

[0050] A porous carbon network comprising chemically interconnected nano-carbon fibers can preferably be obtained by a method for preparing a crystalline carbon network in a reactor 3 containing a reaction zone 3b and a termination zone 3c by the following operations: injecting an oil-in-water or bicontinuous microemulsion c containing metal catalyst nanoparticles into a reaction zone 3b at a temperature above 600°C, preferably above 700°C, more preferably above 900°C, even more preferably above 1000°C, more preferably above 1100°C, preferably at most 3000°C, more preferably at most 2500°C, and most preferably at most 2000°C to prepare a crystalline carbon network e; transferring these networks e to the termination zone 3c; and suspending or stopping the formation of the crystalline carbon network in the termination zone by spraying water d.

[0051] In a more preferred embodiment, the network can be obtained by the above method, wherein the reactor is a furnace carbon black reactor 3, which contains a combustion zone 3a, a reaction zone 3b and a termination zone 3c along the axial direction of the reactor 3, and is carried out by the following operations: burning fuel a in an oxygen-containing gas b in the combustion zone to generate a stream of hot exhaust gas a1, and transferring the exhaust gas al from the combustion zone 3a to the reaction zone 3b; spraying an oil-in-water or bicontinuous microemulsion c containing metal catalyst nanoparticles in the reaction zone 3b containing the hot exhaust gas; carbonizing the emulsion at a temperature above 600°C, preferably above 700°C, more preferably above 900°C, even more preferably above 1000°C, more preferably above 1100°C, preferably at most 3000°C, more preferably at most 2500°C, and most preferably at most 2000°C; and quenching or stopping the reaction in the termination zone 3c by spraying water d to produce a crystalline carbon network e.

[0052] The web is preferably obtainable by the above-described method, wherein further processing details are described in the following section entitled "Method for obtaining a carbon web comprising nanofibers" and in Figure 1A Available in.

[0053] The present invention may alternatively be described as the use of a porous carbon mesh containing chemically interconnected carbon nanofibers for reducing the thickness of a layer containing carbon nanofibers. Alternatively, the present invention may also be described as the use of a porous carbon mesh containing chemically interconnected carbon nanofibers for reducing the thickness of a layer containing carbon nanofibers to less than 1000 μm, preferably less than 750 μm, more preferably less than 500 μm and most preferably less than 350 μm. The present invention may further be described as the use of a porous carbon mesh containing chemically interconnected carbon nanofibers for reducing the thickness of a film containing carbon nanofibers to less than 250 μm, preferably less than 150 μm, more preferably less than 100 μm and most preferably less than 50 μm.

[0054] The present invention can therefore also be described as the use of a porous carbon mesh containing chemically interconnected isotropic nanocarbon fibers in an antistatic layer, static dissipative layer or conductive layer having a thickness of less than 1000 μm. The layer is preferably a polymer layer. Examples of suitable polymers for forming the polymer layer are polypropylene (PP), polyethylene (PE), polyamide (PA), polyvinyl chloride (PVC), polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene (ETFE), polypropylene carbonate (PPC), cellulose triacetate (CTA) and polylactic acid (PLA).

[0055] However, any insulating polymer in which the carbon network of the present invention can be embedded and can be processed into a layer (i.e., a sheet or a film) is suitable for use in the present invention. Typically, polymers without carbon networks are insulators, which means that their volume resistivity is higher than 10 10 Ω.cm, where the volume resistivity is defined in the conventional manner according to ASTM D257. However, the carbon network can also be used to increase the conductivity of any material or layer. Preferably, the material - that is, the material without the carbon network - has a volume resistivity higher than 10 10 Ω.cm, preferably higher than 10 11 Ω.cm and more preferably higher than 10 12 Typically, the volume resistivity of the composite material (i.e., the material including the carbon network) is between 10 0 -10 12 Ω.cm, preferably 10 2 -10 10 Ω.cm, more preferably 10 3 -10 10 Ω.cm and most preferably within 10 4 -10 10 In one embodiment, the volume resistivity of the composite material is within the range of 10 3 -10 8 Ω.cm, preferably 10 4 -10 8 Ω.cm and more preferably 10 4 -10 6 Ω.cm. In an alternative embodiment, the volume resistivity of the composite material is 10 8 -10 12 Ω.cm, preferably 10 8 -10 10 In the range of Ω.cm.

[0056] The addition level of the porous carbon mesh containing chemically interconnected crystalline nano-carbon fibers can be suitably greater than 10% by weight, more preferably at least 15% by weight, even more preferably at least 20% by weight, still more preferably at least 25% by weight and most preferably at least 30% by weight. Alternatively, the addition level is 10 to 45% by weight, more preferably 12 to 35% by weight, even more preferably 14 to 28% by weight and most preferably 16 to 24% by weight. Herein, % by weight is defined in its common sense and refers to a mass percentage or mass fraction normalized to 100%. It is defined as the amount of a specific component (here, the carbon mesh) divided by the sum of all components (here, the layer) and multiplied by 100%.

[0057] application

[0058] In one aspect, the present invention relates to a layer of less than 1000 μm containing at least 10% by weight of a porous carbon mesh containing chemically interconnected isotropic nano-carbon fibers (or in other words, a porous carbon mesh containing chemically interconnected nano-carbon fibers). Alternatively, the layer contains at least 15% by weight, even more preferably at least 20% by weight, still more preferably at least 25% by weight and most preferably at least 30% by weight of the carbon mesh. Alternatively, the level of addition of the carbon mesh is 10 to 50% by weight, more preferably 12 to 45% by weight, even more preferably 15 to 40% by weight and most preferably 20 to 35% by weight, based on the weight of the layer.

[0059] The layer may be a film or sheet as defined above. The layer of the invention is therefore thinner than 1000 μm. Preferably, the layer is thinner than 750 μm, more preferably thinner than 500 μm and even more preferably thinner than 350 μm. The layer may be a film of less than 250 μm, preferably less than 150 μm. Preferably, the film of the invention is thinner than 100 μm, more preferably thinner than 75 μm, even more preferably thinner than 50 μm, still more preferably thinner than 35 μm and most preferably thinner than 25 μm. The layer is preferably at least 0.1 μm, more preferably at least 1 μm, even more preferably at least 2 μm, most preferably at least 5 μm. The layer thickness is determined using a thickness from Non-destructive thickness gauges use magnetic, magnetic induction and eddy current thickness to measure.

[0060] At the above mentioned addition levels, the layers (preferably films) of the present invention may have a 10 Ω.cm, more preferably less than 10 8 Ω.cm, even more preferably less than 10 6 Ω.cm, still more preferably less than 10 4 Ω.cm and most preferably less than 10 0 Ω.cm volume resistivity. Or, the volume resistivity is 10 0 -10 3 , 104 -10 7 Ω.cm or 10 8 -10 10 Ω.cm. In qualitative terms, the layer of the present invention is preferably an antistatic layer, a static dissipative layer, a semiconductive layer or a conductive layer.

[0061] The above-mentioned layer (preferably film) according to the present invention can be used very appropriately in many technical fields. Therefore, the present invention also covers an article comprising the layer of the present invention. The article can be a packaging material, such as an electrostatic protection packaging. Alternatively, the article can be a transport box, a casing or a conductive polymer covering for storing, transporting, protecting or supporting electrical devices and equipment.

[0062] The invention also encompasses layers which have been applied as a coating or as an ink. It may be suitable for use in the preparation of printed electronics or in the repair of antistatic, static dissipative or conductive materials.

[0063] Method for obtaining a carbon mesh comprising carbon nanofibers

[0064] The method for obtaining a porous carbon network containing chemically interconnected nano-carbon fibers can be best described as an improved carbon black manufacturing method, wherein "improved" is understood as providing a suitable oil, preferably an oil containing at least 14 C atoms (>C14) (e.g., carbon black feedstock oil (CBFS)) as part of a single-phase emulsion to the reaction zone of the carbon black reactor, wherein the single-phase emulsion is a thermodynamically stable microemulsion containing metal catalyst nanoparticles. The emulsion is preferably provided to the reaction zone by spraying so that the emulsion is atomized into droplets. Although the method can be carried out batchwise or semi-batchwise, the improved carbon black manufacturing method is advantageously carried out in a continuous process. The single-phase emulsion is a microemulsion containing metal catalyst nanoparticles. The preferred single-phase emulsion contains CBFS oil and can be referred to as "emulsified CBFS" in the context of the present invention.

[0065] The method for preparing a carbon network can be implemented in a reactor 3 containing a reaction zone 3b and a termination zone 3c by the following operations: injecting a single-phase emulsion c, which is a microemulsion containing metal catalyst nanoparticles, preferably an emulsion containing CBFS, into a reaction zone 3b at a temperature above 600°C, preferably above 700°C, more preferably above 900°C, even more preferably above 1000°C, more preferably above 1100°C, preferably up to 3000°C, more preferably up to 2500°C, and most preferably up to 2000°C to produce a porous carbon network containing chemically interconnected nanocarbon fibers; transferring these networks to the termination zone 3c; and abruptly stopping or stopping the formation of a porous carbon network containing chemically interconnected nanocarbon fibers in the termination zone by spraying water d. The single-phase emulsion is preferably sprayed into the reaction zone. Reference Figure 1A .

[0066] Alternatively, the method for preparing a porous carbon network containing chemically interconnected nanocarbon fibers is implemented in a furnace carbon black reactor 3 containing a combustion zone 3a, a reaction zone 3b and a termination zone 3c along the axial direction of the reactor 3 by the following operations: a stream of hot exhaust gas a1 is generated in the combustion zone by burning a fuel a in an oxygen-containing gas b and the exhaust gas a1 is transferred from the combustion zone 3a to the reaction zone 3b; in the reaction zone 3b containing the hot exhaust gas, a single-phase emulsion c according to the present invention, preferably containing a metal catalyst, is sprayed (atomized) A microemulsion of nanoparticles, preferably an emulsion comprising CBFS; carbonizing the emulsion at an increased temperature (at a temperature above 600°C, preferably above 700°C, more preferably above 900°C, even more preferably above 1000°C, more preferably above 1100°C, preferably at most 3000°C, more preferably at most 2500°C, most preferably at most 2000°C); and quenching or stopping the reaction in the termination zone 3c (i.e. the formation of a porous carbon network comprising chemically interconnected nanocarbon fibers) by spraying water d. The reaction zone 3b comprises at least one inlet (preferably a nozzle) for introducing the emulsion, preferably by atomization. Reference Figure 1A .

[0067] The residence time of the emulsion in the reaction zone of the furnace carbon black reactor can be relatively short, preferably in the range of 1 to 1000 ms, more preferably 10 to 100 ms. Longer residence times may have an effect on the properties of the carbon network. An example may be the size of the crystallites, which are larger when longer residence times are used.

[0068] According to conventional carbon black manufacturing methods, the oil phase can be aromatic and / or aliphatic, preferably containing at least 50 wt% C14 or higher, more preferably at least 70 wt% C14 or higher (based on the total weight of the oil). A list of typical oils that can be used, but is not limited to, for obtaining a stable emulsion is carbon black feedstock oil (CBFS), phenol oil, anthracene oil, (short-medium-long chain) fatty acids, fatty acid esters, and paraffin wax. The oil is preferably C14 or higher. In one embodiment, the oil preferably has high aromaticity. In the art, aromaticity is preferably characterized according to the Bureau of Mines Correlation Index (BMCI). The oil preferably has a BMCI greater than 50. In one embodiment, the oil has low aromaticity, preferably having a BMCI < 15.

[0069] In the context of the present invention, CBFS is an economically attractive oil source and is preferably a heavy hydrocarbon mixture mainly containing C14 to C50, and the sum of C14 to C50 preferably totals at least 50 wt%, more preferably at least 70 wt% of the feedstock. Some of the most important feedstocks for preparing carbon black include clarified slurry oil (CSO) obtained from the fluid catalytic cracking of gas oil, ethylene cracker residue from naphtha steam cracking, and coal tar. The presence of paraffin wax (<C15) significantly reduces their suitability, and higher aromaticity is preferred. The concentration of aromatic compounds determines the rate of carbon nucleus formation. The carbon black feedstock preferably has a high BMCI to be able to provide a high yield with minimal heat input, thereby reducing manufacturing costs. In a preferred embodiment, and according to current CBFS specifications, the oil, including mixtures of oils, has a BMCI value greater than 120. Although those skilled in the art can understand what is suitable CBFS, for guidance only, it should be noted that from the perspective of yield, the BMCI value of CBFS is preferably greater than 120, even more preferably greater than 132. The amount of asphaltene in the oil is preferably less than 10 wt%, preferably less than 5.0 wt% of the CBFS weight. CBFS preferably has a low sulfur content because sulfur has an adverse effect on product quality, resulting in a lower yield and corroding equipment.

[0070] Preferably, the sulfur content of the oil according to ASTM D1619 is less than 8.0 wt%, preferably less than 4.0 wt%, more preferably less than 2.0 wt%.

[0071] The emulsion, preferably an emulsion comprising CBFS, is a "single-phase emulsion", which is understood to mean that the oil phase and the aqueous phase appear visually as a miscible mixture, exhibiting no physical separation of oil, water or surfactant to the naked eye. Single-phase emulsions may be macroemulsions or microemulsions, and may be kinetically stable or thermodynamically stable. It is generally believed that the process of complete emulsion breakup (coalescence) (i.e., separation of the system into a major oil phase and an aqueous phase) is governed by four different droplet loss mechanisms, namely Brownian flocculation, creaming, sedimentation flocculation, and disproportionation.

[0072] A "stable single-phase emulsion" in the context of the present invention is understood to mean that, after a period of time exceeding the preparation time of the carbon network, the emulsion does not show visible physical separation, preferably reflected in the fact that the emulsion does not show any pH change of more than 1.0 pH unit and / or does not show any viscosity change of more than 20%. The term "stable" may mean "thermodynamically stable" or "kinetically stable" (by adding energy, i.e., through mixing). In practice, a single-phase emulsion is considered stable if no visible separation occurs, i.e., a single phase is maintained, for a period of at least 1 minute after the preparation of the emulsion. Thus, it is preferred that the emulsion maintains its pH within a range of 1.0 pH unit and / or its viscosity within a range of variation of less than 20% for a period of at least 1 minute, preferably at least 5 minutes after preparation. Although extended stability is preferred for processing purposes, it should be noted that the manufacturing process can still benefit from using an emulsion that is stable within a relatively short time span of 1 minute, preferably 5 minutes: by adding energy (mixing), the stability of the emulsion can be extended, and short-term stability can be extended using in-line mixing. Although the macroemulsion is not thermodynamically stable, and will always revert to its original, immiscible separate oil and water phases, the rate of decomposition can be slow enough to make it kinetically stable over the length of the manufacturing process.

[0073] As long as a stable single-phase emulsion is obtained, the amount of water and oil should not be considered restrictive, but it should be noted that a reduced amount of water (and increased amount of oil) improves the yield. The water content is generally between 5% and 50% by weight of the emulsion, preferably 10 to 40% by weight, even more preferably up to 30% by weight, more preferably 10 to 20% by weight of the emulsion. Although larger amounts of water may be considered, this will be at the expense of yield. Without wishing to be bound by any theory, the inventors believe that the water phase affects the shape and morphology of the mesh thus obtained.

[0074] The choice of surfactant should not be considered a limiting factor, provided that the combination of oil, water and surfactant produces a stable microemulsion as defined above. As a further guide to the skilled person, it should be noted that the surfactant can be selected based on the hydrophobicity or hydrophilicity of the system, i.e. the hydrophilic-lipophilic balance (HLB). The HLB of a surfactant is a measure of the degree of hydrophilicity or lipophilicity of the surfactant, determined by calculating values ​​for different regions of the molecule according to the Griffin or Davies method. Suitable HLB values ​​depend on the type of oil and the amount of oil and water in the emulsion, and can be easily determined by the skilled person based on the need to maintain a thermodynamically stable single-phase emulsion as defined above. It has been found that emulsions containing more than 50% by weight of oil, preferably with less than 30% by weight of an aqueous phase, are best stabilized with surfactants having HLB values ​​greater than 7, preferably greater than 8, more preferably greater than 9, and most preferably greater than 10. On the other hand, emulsions with up to 50% by weight of oil are preferably stabilized with surfactants having an HLB value of less than 12, preferably less than 11, more preferably less than 10, most preferably less than 9, and especially less than 8. Preferably, the surfactant is selected to be compatible with the oil phase. In the case of an emulsion containing CBFS, where the oil is a CBFS, surfactants with high aromaticity are preferred, while oils with low BMCI, for example characterized by BMCI <15, are preferably stabilized with aliphatic surfactants. The surfactant may be cationic, anionic or nonionic, or a mixture thereof. One or more nonionic surfactants are preferred in order to increase the yield, since no residual ions are left in the final product. In order to obtain a clean tail gas stream, the surfactant structure preferably has a low sulfur and low nitrogen content, preferably no sulfur and nitrogen. Non-limiting examples of typical nonionic surfactants that can be used to obtain stable emulsions are the commercially available Tween, Span, Hypermer, Pluronic, Emulan, Neodol, Triton X and Tergitol series.

[0075] In the context of the present invention, a microemulsion is a dispersion made of water, oil (preferably CBFS) and a surfactant, which is a single optically stable and thermodynamically stable liquid with a dispersed domain diameter varying approximately in the range of 1 to 500 nm, preferably 1 to 100 nm, typically 10 to 50 nm. In a microemulsion, the domains of the dispersed phase are either spherical (i.e. droplets) or interconnected (to obtain a bicontinuous microemulsion). In a preferred embodiment, the surfactant tail forms a continuous network in the oil phase of a water-in-oil (w / o) emulsion or a bicontinuous emulsion. These water domains should contain a metal catalyst, preferably a metal catalyst having an average particle size between 1 nm and 100 nm.

[0076] The single-phase emulsion (i.e. w / o or bicontinuous microemulsion, preferably bicontinuous microemulsion) further comprises metal catalyst nanoparticles preferably having an average particle size between 1 nm and 100 nm. The skilled person will find sufficient guidance in the field of carbon nanotubes (CNTs) to prepare and use these types of nanoparticles. It has now been found that these metal nanoparticles improve network formation in terms of both rate and yield and reproducibility. Methods for making suitable metal nanoparticles are described in Vinciguerra et al., "Growth mechanisms in chemical vapour deposited carbon nanotubes", Nanotechnology (2003) 14, 655; Perez-Cabero et al., "Growing mechanism of CNTs: a kinetic approach", J. Catal. (2004) 224, 197-205; Gavillet et al., "Microscopic mechanisms for the catalyst assisted growth of single-wall carbon nanotubes", Carbon. (2002) 40, 1649-1663; and Amelinckx et al., "A formation mechanism for catalytically grown helix-shaped graphite nanotubes", Science (1994) 265, 635-639, the contents of which are incorporated herein by reference for the preparation of metal nanoparticles.

[0077] The metal catalyst nanoparticles are used in a bicontinuous or w / o microemulsion, preferably a bicontinuous or w / o microemulsion comprising CBFS. In one embodiment, a bicontinuous microemulsion is most preferred. Advantageously, the uniformity of the metal particles in the (bicontinuous) microemulsion is controlled by mixing a first (bicontinuous) microemulsion and a second (bicontinuous) microemulsion, wherein the aqueous phase in the first (bicontinuous) microemulsion contains a metal complex salt that can be reduced to the final metal particles, and the aqueous phase in the second (bicontinuous) microemulsion contains a reducing agent that can reduce the metal complex salt; when mixed, the metal complex is reduced to form metal particles. The controlled (bicontinuous) emulsion environment stabilizes the particles against agglomeration or Ostwald ripening. The size, concentration and durability of the catalyst particles are easily controlled. Routine experiments are considered to adjust the average metal particle size within the above range, for example by changing the molar ratio of metal precursor to reducing agent. An increase in the relative amount of reducing agent produces smaller particles. The metal particles thus obtained are monodisperse, preferably within 10% and more preferably within 5% of the average particle size. In addition, the present invention does not provide constraints on the actual metal precursor, as long as the precursor can be reduced. Non-limiting examples of nanoparticles included in the carbon mesh containing nanocarbon fibers are noble metals (Pt, Pd, Au, Ag), iron group elements (Fe, Co and Ni), Ru and Cu. Suitable metal complexes can be: (i) platinum precursors, such as H 2 PtCl 6 ;H 2 PtCl 6 .xH 2 O;K 2 PtCl 4 ; K 2 PtCl 4 .xH 2 O;Pt(NH 3 ) 4 (NO 3 ) 2 ; Pt(C 5 H 7 O 2 ) 2 , (ii) a ruthenium precursor, such as Ru(NO)(NO 3 ) 3 ;Ru(dip) 3 Cl 2 [dip=4,7-diphenyl-1,10-phenanthroline]; RuCl 3 , or (iii) a palladium precursor, such as Pd(NO 3 ) 2 , or (iv) a nickel precursor such as NiCl 2 or NiCl 2.xH 2 O;Ni(NO 3 ) 2 ;Ni(NO 3 ) 2 .xH 2 O;Ni(CH 3 COO 2 ; Ni(CH 3 COO 2 .xH 2 O;Ni(AOT) 2 [AOT = bis (2-ethylhexyl) sulfosuccinate], wherein x can be any integer selected from 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 and is typically 6, 7 or 8. Non-limiting suitable reducing agents are hydrogen, sodium borohydride, sodium bisulfate, hydrazine or hydrazine hydrate, ethylene glycol, methanol and ethanol. Citric acid and dodecylamine are also suitable. The type of metal precursor is not an essential part of the present invention. The metal of the particles of the (bicontinuous) microemulsion is preferably selected from Pt, Pd, Au, Ag, Fe, Co, Ni, Ru and Cu and mixtures thereof in order to control the morphology of the carbon structure network finally formed. The metal nanoparticles are ultimately embedded in these structures, where the metal particles are physically attached to these structures. Although there is no minimum metal particle concentration for forming these networks - in fact, the networks are formed using the improved carbon black manufacturing method according to the present invention - it is found that the yield increases with the metal particle concentration. In a preferred embodiment, the active metal concentration is at least 1 mM, preferably at least 5 mM, preferably at least 10 mM, more preferably at least 15 mM, more preferably at least 20 mM, in particular at least 25 mM, most preferably at most 3500 mM, preferably at most 3000 mM. In one embodiment, the metal nanoparticles comprise at most 250 mM. These are concentrations of catalyst relative to the amount of aqueous phase of the (bicontinuous) microemulsion.

[0078] Atomization of the single-phase emulsion, preferably an emulsion comprising CBFS, is preferably achieved by spraying using a nozzle system 4, which allows the emulsion droplets to contact with the hot exhaust gas a1 in the reaction zone 3b, resulting in conventional carbonization, network formation and subsequent agglomeration to produce the carbon network of the present invention. The injection step preferably involves an elevated temperature above 600°C, preferably between 700°C and 3000°C, more preferably between 900°C and 2500°C, more preferably between 1100°C and 2000°C.

[0079] In one aspect, the porous carbon network comprising chemically interconnected nanofibers preferably has at least one, preferably at least two, more preferably at least three, and most preferably all of the following properties:

[0080] (i) an iodine adsorption value (IAN) of at least 30 mg / g, preferably at least 50 mg / g, more preferably at least 100 mg / g and most preferably at least 150 mg / g according to ASTM D1510. Alternatively, the IAN is from 30 to 1000 mg / g, preferably from 100 to 800 mg / g, more preferably from 30 to 500 mg / g according to ASTM D1510;

[0081] (ii) At least 30 m according to ASTM D6556 2 / g, preferably at least 50m 2 / g, more preferably at least 100m 2 / g and most preferably at least 150m 2 / g nitrogen surface area (N2SA). Alternatively, according to ASTM D6556, the N2SA is 30 to 1000 m 2 / g, preferably 100 to 800m 2 / g and more preferably 30 to 500 m 2 / g;

[0082] (iii) At least 40 m according to ASTM D6556 2 / g, more preferably at least 70m 2 / g, even more preferably at least 100m 2 / g, even more preferably at least 125m 2 / g and most preferably at least 150m 2 / g statistical thickness surface area (STSA). Alternatively, according to ASTM D6556, STSA is 40 to 1000 m 2 / g, preferably 100 to 800m 2 / g, more preferably 120 to 500 m 2 / g;

[0083] (iv) an Oil Adsorption Number (OAN) according to ASTM D2414 of at least 50 cc / 100 g, preferably at least 75 cc / 100 g, more preferably at least 100 cc / 100 g, even more preferably at least 125 cc / 100 g, and most preferably at least 150 cc / 100 g. Alternatively, an OAN of 50 to 500 cc / 100 g, preferably 150 to 350 cc / 100 g, according to ASTM D2414,

[0084] in:

[0085] IAN = Iodine Adsorption Number: grams of iodine adsorbed per kilogram of carbon black under specified conditions as defined in ASTM D1510;

[0086] N2SA = Nitrogen Surface Area: The total surface area of ​​carbon black calculated from nitrogen adsorption data using BET theory according to ASTM D6556;

[0087] STSA = Statistical Thickness Surface Area: the external surface area of ​​carbon black calculated from nitrogen adsorption data using de Boer theory and the carbon black model according to ASTM D6556; and

[0088] OAN = Oil Adsorption Number: The number of cubic centimeters of dibutyl phthalate (DBP) or paraffin oil adsorbed by 100 g of carbon black under specified conditions. The OAN value is proportional to the degree of aggregation at the structural level of the carbon black determined according to ASTM D2414.

[0089] For each of IAN, N2SA (or NSA), STSA and OAN, all of which are typical parameters for characterizing carbon black materials, the porous carbon mesh containing chemically interconnected nanocarbon fibers exhibits superior properties compared to conventional carbon black. The porous carbon mesh containing chemically interconnected nanocarbon fibers is preferably characterized by at least one, preferably at least two, and more preferably all of (i), (ii) and (iii), because they are typical ways to characterize the surface area properties of the material. In one embodiment, the porous carbon mesh containing chemically interconnected nanocarbon fibers exhibits at least one of (i), (ii) and (iii), and further complies with (iv).

[0090] Method for preparing film or sheet

[0091] Film or lamella according to the present invention can be prepared by any suitable method known to the technician. For example, film or lamella can be manufactured via cast film extrusion. In this method, the polymer melt comprising porous carbon mesh comprising chemically interconnected nano-carbon fibers is pushed through a flat die or a slot die to form a film or lamella with a desired thickness. If necessary, for example, when coextrusion, a feed block can be used.

[0092] Alternatively, a blown film extrusion process can be used to prepare the film. Here, a polymer melt containing a porous carbon mesh containing chemically interconnected nanocarbon fibers is pushed through a generally vertical annular slit die to form a thin-walled tube. Air is introduced via a hole in the center of the die to inflate the tube (e.g., like a balloon). If necessary, a high-speed air ring can be used to blow cold air onto the hot film to cool it.

[0093] Example

[0094] Example 1: Electrical conductivity of a polymer material comprising a carbon mesh containing carbon nanofibers

[0095] Using a blown film extrusion method using a blowing device BL 50T with a die length of 30mm (in the case of 25 wt% carbon mesh) or using a cast film extrusion method using a cooling roller CR 72T (in the case of 30 wt% or 35 wt% carbon mesh), a 50 μm thick polypropylene copolymer (PPC, Moplen EP340M) layer containing 25 wt%, 30 wt% or 35 wt% of a carbon mesh containing nanocarbon fibers is prepared. A carbon mesh prepared using a manufacturing method similar to Example 1 in WO2018 / 002137 (the contents of which are incorporated herein by reference). The average particle intrapore diameter of the mesh is measured to be 20 nm using mercury intrusion porosimetry (ASTM D4404-10). The melt was prepared using a single screw extruder (Colllin; Model Teach Line E20T; 42 L / D line; D=26 mm) set at 90 rpm for blown film extrusion and 60 rpm for cast film extrusion.

[0096] Table 1 shows the transverse and longitudinal surface resistivity of the film as the carbon mesh addition level changes. It can be seen that the surface resistivity in both the transverse and longitudinal directions gradually decreases as the carbon mesh addition level increases. The surface resistivity is measured with the aid of a Keithley picoammeter.

[0097] Table 1: Transverse and longitudinal surface resistivity versus carbon network addition level.

[0098]

[0099]

[0100] Example 2: Viscosity of a polymer material comprising a carbon mesh containing carbon nanofibers

[0101] The carbon mesh of the present invention is used to prepare antistatic films, static dissipative films or conductive films. For such films, (close to) penetration of the conductive filler is required, which is usually accompanied by a significant reduction in the melt flow index (MFI) = increased viscosity. It has been found that with the carbon mesh of the present invention, the melt flow is not as much impaired as with carbon black (CB). A reduction in the melt flow index (MFI) means an increase in viscosity, which limits the ability to further process the mixture. Especially for drawn films, this is a key parameter to obtain a uniform film (same thickness and properties).

[0102] Table 2 shows MFI data according to ISO standard 1133-2005, where PPC (PP copolymer) containing the carbon mesh of the present invention is compared with PPC (PP copolymer) containing CB Vulcan XC72 (special CB, commonly used in EC applications). A carbon mesh prepared using a manufacturing method similar to Example 1 in WO2018 / 002137 (the content of which is incorporated herein by reference). A reduction in MFI means an increase in viscosity. Compared with CB with the same loading, the carbon mesh of the present invention contained in PPC produces a compound with a lower viscosity. This means that conductive films can be prepared using the carbon mesh of the present invention, while the use of carbon black is likely to fail, especially at low thicknesses.

[0103] Table 2: MFI data for PPCs comprising CB or carbon networks of the invention.

[0104]

[0105] *Measured at 230°C, 5 kg.

Claims

1. Use of a porous carbon network comprising chemically interconnected nanocarbon fibers for reducing the thickness of an antistatic layer, static dissipative layer or conductive layer to a thickness of less than 500 μm, wherein the carbon network is contained in the layer and is an intraparticle porous network, wherein the nanocarbon fibers are interconnected with other nanocarbon fibers in the network via junctions by chemical bonds, wherein the pores in the network have an intraparticle pore diameter of 5-150 nm, as determined using mercury intrusion porosimetry according to ASTM D4404-10; wherein at least 20% by weight of the carbon in the carbon network is in crystalline form, and the nanocarbon fibers have an average aspect ratio of fiber length to thickness of at least 2.

2. The use according to claim 1, wherein the use is for increasing the conductivity of an antistatic layer, a static dissipative layer, a semiconductive layer or a conductive layer.

3. Use according to any one of the preceding claims, wherein the carbon network is incorporated at a level greater than 10% by weight of the layer.

4. The use according to claim 1, wherein the average fiber length of the nanocarbon fiber is 30-10,000 nm.

5. Use according to claim 1, wherein the layer is a polymer layer.

6. The use according to claim 1, wherein the volume resistivity is 10 0 -10 10 Ω.cm.

7. The use according to claim 1, wherein the carbon network can be obtained by a method for preparing a crystalline carbon network in a reactor 3 containing a reaction zone 3b and a termination zone 3c by the following operations: injecting an oil-in-water or bicontinuous microemulsion c containing metal catalyst nanoparticles into the reaction zone 3b at a temperature above 600°C to prepare a crystalline carbon network e; transferring these networks e to the termination zone 3c; and abruptly stopping or stopping the formation of the crystalline carbon network in the termination zone by spraying water d.

8. Use according to claim 7, wherein the reaction zone 3b is at a temperature above 700°C.

9. Use according to claim 7, wherein the reaction zone 3b is at a temperature above 900°C.

10. The use according to claim 7, wherein the reaction zone 3b is at a temperature above 1000°C.

11. The use according to claim 7, wherein the reaction zone 3b is at a temperature above 1100°C.

12. The use according to claim 7, wherein the reaction zone 3b is at a temperature of at most 3000°C.

13. The use according to claim 7, wherein the reaction zone 3b is at a temperature of at most 2500°C.

14. Use according to claim 7, wherein the reaction zone 3b is at a temperature of at most 2000°C.

Citation Information

Patent Citations

  • Broadening of percolation slope in conductive carbon black compositions with at least one non-conductive polymer

    WO2014108876A2

  • Production of crystalline carbon structure networks

    WO2018002137A1